A novel use of cardiac resynchronization therapy‐defibrillator device in hypertrophic cardiomyopathy. Issue 1 (30th May 2018) - Cay, Serkan; Ozeke, Ozcan; Ozcan, Firat; Aras, Dursun; Topaloglu, Serkan
Abstract: Dual‐chamber implantable cardioverter‐defibrillator is generally used in patients with atrioventricular block and hypertrophic cardiomyopathy with preserved left ventricular ejection fraction. In the current case, a cardiac resynchronization therapy‐defibrillator device was implanted in a patient with non‐obstructive hypertrophic cardiomyopathy with preserved ejection fraction and atrioventricular block to achieve both more physiological pacing and life‐threatening ventricular arrhythmia management.